An overview of idiopathic optic neuritis in eastern Nepal - Das, H; Gautam, Maria; Lavaju, P (Nepalese Journal of Ophthalmology, 2010)
Background: Inflammation of the optic nerve is a common cause of visual loss due to optic nerve pathology. Objective: To report the clinical features, demographic pattern and response to pulse steroid therapy in patients with idiopathic optic neuritis in eastern Nepal. Materials and methods: The hospital data of patients with idiopathic optic neuritis admitted to the department of ophthalmology in a tertiary level center in eastern Nepal between Jan 2000 to Dec 2006 were retrospectively analyzed. The parameters studied were demographic pattern, clinical features, visual acuity and field defects. Results: Thirty-six patients (52 eyes) were found to have optic neuritis (papillits in 36 and retrobulbar optic neuritis in16 eyes). The male to female ratio was1.25:1. The mean age of the patients was 33.56±17.88 years (95 % CI=24.66 - 42.45). The most common modes of presentation were loss of visual acuity and color vision defect. One patient had features suggestive of multiple sclerosis. Vision improved in 42 eyes at discharge from the hospital. Response to pulse methylprednisolone therapy was good in most (42 eyes) of the cases except for the patients having initial visual acuity of no light perception. Conclusion: Response to pulse methylprednisolone therapy is good in patients with initial visual acuity of at least perception of light. Demographic and clinical features of our patients were different from those reported from the western world. Some similarity was observed between studies reported from the oriental countries. Keywords: optic neuritis; demographic pattern; pulse steroid therapy. DOI: 10.3126/nepjoph.v2i1.3698 Nep J Oph 2010;2(1):10-15